Toxicity Studies on Graphene-Based Nanomaterials in Aquatic Organisms: Current Understanding - Nemi Malhotra; Oliver B. Villaflores; Gilbert Audira; Petrus Siregar; Jiann-Shing Lee; Tzong-Rong Ger; Chung-Der Hsiao (Molecules, 2020)
Graphene and its oxide are nanomaterials considered currently to be very promising because of their great potential applications in various industries. The exceptional physiochemical properties of graphene, particularly thermal conductivity, electron mobility, high surface area, and mechanical strength, promise development of novel or enhanced technologies in industries. The diverse applications of graphene and graphene oxide (GO) include energy storage, sensors, generators, light processing, electronics, and targeted drug delivery. However, the extensive use and exposure to graphene and GO might pose a great threat to living organisms and ultimately to human health. The toxicity data of graphene and GO is still insufficient to point out its side effects to different living organisms. Their accumulation in the aquatic environment might create complex problems in aquatic food chains and aquatic habitats leading to debilitating health effects in humans. The potential toxic effects of graphene and GO are not fully understood. However, they have been reported to cause agglomeration, long-term persistence, and toxic effects penetrating cell membrane and interacting with cellular components. In this review paper, we have primarily focused on the toxic effects of graphene and GO caused on aquatic invertebrates and fish (cell line and organisms). Here, we aim to point out the current understanding and knowledge gaps of graphene and GO toxicity.